National tourism and its role in the Post-COVID economic recovery of the Mexican Regions - Andrés Rosales, Roldán; De Jesús Almonte, Leobardo; Quintana Romero, Luis; Álvarez García, José (El Periplo Sustentable, 2023)
Tourism is an important activity not only for generating employment in Mexico, but for the growth of those regions focused on this sector. The prevailing insecurity in the different Mexican states influenced the flow of international tourism, which in addition to the pandemic, further complicated the growth of the sector. These two problems, insecurity and the COVID-19 pandemic, affected and aggravated the growth dynamics of the different tourist regions. This research aims to obtain empirical evidence that the recovery of the sector after the COVID-19 Pandemic is found more in national tourism than in international tourism. The methodology used is the approach and estimation of Spatial Autoregressive Vectors (SpVAR) models with quarterly information for the period 2003:01-2020:04. The results show that national tourism served as a buffer against the fluctuations of international tourism in the study period. It is also observed that tourism is one of the sectors that will recover more quickly post-pandemic due to the confidence of the population of origin. In this research, two socio-economic variables of great repercussion in this sector are considered, COVID-19 and citizen insecurity. There are few investigations that consider both variables together. Provides relevant information for decision-making and implementation of economic policies by public managers, managers of the tourism sector and the business sector, to strengthen the growth of the tourism sector in Mexico. Policies that guide tourism recovery in order to overcome the serious crisis in tourism demand caused by COVID-19.